How Do We Measure Oral Health Literacy? (Turkey Health Literacy Journal, 2021)
This study aimed to review the measurement tools developed for the determination of oral health literacy (OHL) and to evaluate the dimensions of measurement by determining the properties of tools. Publications in PubMed, Scopus, Web of Science, CINAHL and Medline electronic databases until January 2021 were screened to determine studies which were conducted for the development or adaptation of OHL scales or tools. The keywords: oral, dental, health, literacy, knowledge, instrument, tool, scale were used. Measurement tools were examined according to six dimensions: 1- reading/pronounciation; 2- reading comprehension or comprehension; 3- numerical skill; 4- oral health knowledge; 5- conceptual oral health knowledge; and 6- decision-making. 37 studies and 38 measurement tools were included in acoordance with the criteria. The most commonly used measurement tools have been developed based on REALM, TOFHLA and HeLMS. Most of the tools measure the dimensions of the ability of reading or pronounciation, numerical skills and reading comprehension skills, and a few measurement tools evaluate oral health knowledge and decision-making dimensions. While assessing OHL, it is recommended to develop comprehensive and critical measurement tools in addition to the ones that determine only reading and numerical skills, and to be use more widely to evaluate the relationship between OHL and oral health-related behaviors.